Improving microwave-assisted hydrothermal degradation of PCDD/Fs in fly ash with added Na2HPO4 and water-washing pretreatment. (April 2019) - Qiu, Qili; Chen, Qian; Jiang, Xuguang; Lv, Guojun; Chen, Zhiliang; Lu, Shengyong; Ni, Mingjiang; Yan, Jianhua; Lin, Xuliang; Song, Huibo; Cao, Junjun
Abstract: In this work, microwave-assisted hydrothermal process is applied to the PCDD/F degradation of municipal solid waste incineration (MSWI) fly ash. The effects of water-washing pretreatment and the Na2 HPO4 reagent on the degradation efficiency of PCDD/Fs are investigated. The PCDD/F content in MSWI fly ash is detected by high-resolution gas chromatography-mass spectrometry (HRGC/MS). The experimental results show that the efficiency of total PCDD/F degradation increases from 60.6% to 83.3% after water-washing pretreatment, with 5 wt % Na2 HPO4 added for 2 h of microwave heating at 220 °C. With more Na2 HPO4 (10 wt %), the degradation efficiency of PCDD/Fs reaches 91.8%, and remarkably, the WHO-TEQ is as low as 0.255 ng g −1 . Analysis of the degradation pathway of PCDD/Fs indicates that a chlorination reaction happens during the microwave-assisted hydrothermal process, as do dechlorination and destruction reactions. Water-washing effectively weakens the chlorination reaction for the decrease of chlorine in fly ash, which contributes to PCDD/F degradation. The reagent Na2 HPO4 has a greater effect on the dechlorination of high-chlorinated congeners. Furthermore, the results indicate that the removal efficiency of PCDDs is higher than that of PCDFs under microwave conditions. Several linear correlations between indicative congener content and I/WHO-TEQ values are summarized. Overall, microwave-assisted hydrothermal process is a promising disposal method and should receive further study for large-scale application. Highlights: Microwave accelerates the PCDD/F degradation. Water-washing greatly increases the degradation of PCDD/Fs. Degradation efficiency of PCDD/Fs reaches 91.8% with Na2 HPO4 added.